Relationship Between Self-Perceived Health, Vitality, and Posttraumatic Growth in Liver Transplant Recipients - Funuyet-Salas, Jesús; Martín-Rodríguez, Agustín; Borda-Mas, Mercedes; Avargues-Navarro, María Luisa; Gómez-Bravo, Miguel Ángel; Romero-Gómez, Manuel; Conrad, Rupert; Pérez-San-Gregorio, María Ángeles (Frontiers in Psychology, 2019)
Our objective was to analyze the differences in posttraumatic growth in 240 liver transplant recipients based on two factors. First, self-perceived health: better (Group 1=G1) and worse (Group 2=G2). Second, vitality: more (Group 3=G3) and less (Group 4=G4). The Posttraumatic Growth Inventory, SF-36 Health Survey (Item 2) and SF-12 Health Survey (vitality dimension) were used. Firstly, analyzing main effects recipients with better (G1) compared to worse (G2) self-perceived health, showed greater posttraumatic growth. Interaction effects were found on essential posttraumatic growth domains such as new possibilities (p = 0.040), personal strength (p=0.027), and appreciation of life (p=0.014). Statistically significant differences showed that among transplant recipients with worse self-perceived health (G2), those with more vitality had higher levels on abovementioned posttraumatic growth dimensions. However, in transplant recipients with better self-perceived health (G1) respective dimensions were not significantly influenced by the level of vitality. Among the recipients with less vitality (G4), those with better self-perceived health showed higher scores on abovementioned posttraumatic growth dimensions. We conclude that positive self-perceived health might compensate for a lack of vitality as well as a high level of vitality may compensate for negative self-perceived health regarding the development of crucial aspects of posttraumatic growth after liver transplantation.